Pengaruh Knowledge Management Terhadap Kinerja Sumber Daya Manusia Dengan Artificial Intelligence Sebagai Variabel Moderasi di PT. Telekomunikasi Selular (Telkomsel) Wilayah Pekanbaru - Ustha, Endrianto (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to determine the influence of Knowledge Management on human resource performance moderated by Artificial Intelligence at PT. Cellular Telecommunications (Telkomsel) Pekanbaru area. This research uses quantitative methods. The population in this study is all employees at GraPARI Telkomsel Pekanbaru area who deal directly with customers and master product knowledge. The sample used in this study was 41 GraPARI Telkomsel Pekanbaru employees. The research data was obtained from the results of filling out a questionnaire with a 5-point likert scale and analyzed using the SEM PLS analysis technique with the help of the SmartPLS program. The results of this study prove that Knowledge Management has a role in improving human resource performance, the better the level of Knowledge Management will make employee performance higher. Employees with work experience in their fields play an important role in Knowledge Management by transferring knowledge to other employees to improve employee performance. Artificial Intelligence moderates the role of Knowledge Management on human resource performance. Artificial Intelligence is able to automate some repetitive work so as to increase the efficiency of employee performance to focus more on handling more complex problems.